Systematic Review: How the Reading Aloud Strategy Still Used in the Last Five Years - Nirwana, Iin; Mahmudah, Khotimah; Pratama, Aryawira (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
The main objective of this study is to explore a study of Reading Aloud Strategy in Teaching English as a Foreign Language (EFL) and its relevance in contemporary educational settings. This research specifically addresses the following objectives: to identify the implications of RA implementation, determine the most effective strategies for its application, and evaluate its effectiveness across different educational levels. Data in the form of articles retrieved through internet search engines at the last five years; between 2018 and 2022. Key search terms included